(untitled) (Marketing Journal, 2025)
This article discusses various theoretical approaches to segmenting taxpayer activities and developing tax risk analysis in determining and managing tax risk. The financial activities of any subject are fraught with risks. To reduce the consequences of ris ks, it is necessary to produce an effective risk management system. The identification, management, elimination of tax risks, mitigation of tax risks in the framework of our observations determines the insufficient development of the system, the need for a more thorough study of tax risks. The article discusses issues of segmentation of taxpayer activities and the stages of their identification.